2001
DOI: 10.1192/apt.7.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for dementia

Abstract: There is little doubt that dementia is a very common cause of disability and dependency in our society. Since dementia of whatever type is usually more common with increasing age, then as population demographics change, so will the prevalence of dementia. Dementia is a generic term and the objective for clinicians, once dementia is suspected, is to attempt to define the cause. Alzheimer's disease is the most common cause of dementia, and in most centres vascular dementia would feature as the next most common a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 45 publications
2
55
0
3
Order By: Relevance
“…The prevalence of dementia in this study (12.9%) is similar to reported studies from Canada 8% [26], Italy 9.8% [27] and Netherlands 13.3% [28], but much higher than a previous hospital based study in Saudi Arabia 0.2% [12] and other countries. Farrag et al, 1998, [29] reported a prevalence of 4.5 % in As suit governorate-Egypt.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of dementia in this study (12.9%) is similar to reported studies from Canada 8% [26], Italy 9.8% [27] and Netherlands 13.3% [28], but much higher than a previous hospital based study in Saudi Arabia 0.2% [12] and other countries. Farrag et al, 1998, [29] reported a prevalence of 4.5 % in As suit governorate-Egypt.…”
Section: Discussionsupporting
confidence: 87%
“…Vascular dementia accounts for 24-48% of dementing illness in the older patients, an incidence of 6-10 in 10,000 per year in those older than 70 years [1] . The prevalence of dementia increased exponentially with age from 12.7% per year in the 90-94 years of age, to 21.2% per year in the 40.7% per year in the 100+ years of age [37] .…”
Section: Public Health Implicationmentioning
confidence: 99%
“…The prevalence of dementia is increasing dramatically worldwide, but the types of dementia vary between countries [1] . Alzheimer disease is the most common type of dementia in Western countries, whereas vascular dementia is more common in Asia [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Females have been shown to be at increased risk for dementia in developed regions as well as Asian countries, but this association was not clear for African and Latin American countries. 3 Hormonal factors have been implicated in the differential risk of women 53 , however other protective factors may exist that are unique to women in developing countries; identification of such factors could be useful in reducing the risk to women in developed countries.…”
Section: Demographic Risk Factorsmentioning
confidence: 99%